2023
DOI: 10.1029/2022gb007518
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Marine CO2‐Carbonate Chemistry in the Northern Antarctic Peninsula

Abstract: The Bransfield Strait is a climate change hotspot at the tip of the northern Antarctic Peninsula (NAP). The region is marked by a mixture of relatively warm waters from the Bellingshausen Sea with cold shelf waters from the Weddell Sea. Additionally, its deep central basin (>800 m) preserves seawater properties from the north‐western Weddell Sea continental shelf. This study assessed long‐term changes in carbonate chemistry in the Bransfield Strait and found that the hydrographic setting (i.e., a mixture betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…Circumpolar Deep Water is a relatively old water mass mainly sourced from mixing along the Antarctic Circumpolar Current between the North Atlantic Deep Water and deep waters from Indian and South Pacific Oceans (Ferreira and Kerr 2017), so it is low in dissolved oxygen and rich in remineralized carbon and macronutrients (Prézelin et al 2000; Hauri et al 2015). Hence, the northern Antarctic Peninsula is constantly influenced by Circumpolar Deep Water intrusions (Barlett et al 2018; Wang et al 2022), altering the biogeochemical dynamics in this region (Henley et al 2019; Orselli et al 2022; Santos‐Andrade et al 2023). The Circumpolar Deep Water is a relatively warm water mass (> 1°C) that intrudes into the intermediate layers along the northern Antarctic Peninsula (Prézelin et al 2000; Venables et al 2017).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Circumpolar Deep Water is a relatively old water mass mainly sourced from mixing along the Antarctic Circumpolar Current between the North Atlantic Deep Water and deep waters from Indian and South Pacific Oceans (Ferreira and Kerr 2017), so it is low in dissolved oxygen and rich in remineralized carbon and macronutrients (Prézelin et al 2000; Hauri et al 2015). Hence, the northern Antarctic Peninsula is constantly influenced by Circumpolar Deep Water intrusions (Barlett et al 2018; Wang et al 2022), altering the biogeochemical dynamics in this region (Henley et al 2019; Orselli et al 2022; Santos‐Andrade et al 2023). The Circumpolar Deep Water is a relatively warm water mass (> 1°C) that intrudes into the intermediate layers along the northern Antarctic Peninsula (Prézelin et al 2000; Venables et al 2017).…”
Section: Figmentioning
confidence: 99%
“…The Dense Shelf Water is advected into the northern Antarctic Peninsula and retained with its most pure form mainly in the deep layer of the central basin of Bransfield Strait (Dotto et al 2016), while an intense mixing changing its physical (Damini et al 2022; Wang et al 2022) and biogeochemical (Santos‐Andrade et al 2023) properties occurs with modified Circumpolar Deep Water at upper levels. Hence, while modified Circumpolar Deep Water is transported from the south at intermediate layers along the northern Antarctic Peninsula, the Dense Shelf Water is advected in deeper layers from the north (Moffat and Meredith 2018; Wang et al 2022).…”
Section: Figmentioning
confidence: 99%
“…The Antarctic Peninsula and its adjacent seas are the most studied Southern Ocean regions due to their remarkable response to global climate change (Flexas et al., 2022; Sato et al., 2021). Studies have shown an increase in the carbon sink potential of the continental Shelf water (SW) of this region (Brown et al., 2019; Shadwick et al., 2021), and certain part of this region is almost close to CO 2 saturation (Santos‐Andrade et al., 2023). The CO 2 source and sink characteristics are influenced by the hydrographic structure and phytoplankton community composition (Damini et al., 2023).…”
Section: Introductionmentioning
confidence: 99%